PSIKOLOGI KEMANUSIAAN PENGATURAN RUANG KELAS - Suhita, Damayanti (Transformasi, 2012)
Abstrad Teaching activities should be designed to support self actualize. It should offer the possibility of developing krativitas and spontaneity, as well as minimizing fear as a tool to motivate. Should students be allowed to make decisions and to live with the consequences of that decision. The view of humanity in the school is very different from the other perspective. The ultimate goal is that in order to provide a more pleasant classroom for teachers danmurid students. The disadvantage is that when taken in excess, can cause a lack of humanity procedure command and power struggles (chaos). Human psychology requires a balance of implementation and these principles can lead to arrangements classrooms be more effective. Key wordÂ  : Human; Psychologi; Classroom Setting.